Pedagogy in an oppressed state: A Multilevel Analysis of Learning in the International Development of Ecuador’s Official Intercultural Bilingual Education. - Terry, Herbert Guy (2014)
The Ecuadorian State underwent a series of new learning experiences in the twentieth century that disrupted its traditional socio-economic order, the rungs of which were ethnically-coded. This study illustrates how domestic and international changes generated new learning for the State, how this learning facilitated an aperture to indigenous movement leaders in a national literacy campaign, and how this inclusion, in turn, supported their own learning and their trajectory as activists for further change. Among their clearest triumphs was the institutionalization of a semi-autonomous Intercultural Bilingual Education system. The education occurring in a rural high school founded within this system is also examined. By revealing learning’s impacts across this spectrum, from the most global to the most local of contexts, this research sheds light on the mutual constitution of these different social spheres. It provides a critical constructivist account of institutional change, and considers whether the learning that caused this change has been more uncritical or critical, more oppressive or liberating.